HUBUNGAN CURAH HUJAN, SUHU UDARA, KELEMBABAN UDARA, KEPADATAN PENDUDUK DAN LUAS LAHAN PEMUKIMAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI KOTA MALANG PERIODE TAHUN 2002-2011 - Gustina Fajarwati Sihombing; irnawati marsaulina; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
The relation of rainfall, temperature, humidity, population density and area of settlement with Dengue Hemorrhagic Fever (DHF)cases in Malang during the period of 2002-2011. DHF was a public health problem in Indonesia. Malang was endemic dengue area located in the highlands. Environmental conditions was one of DHF cases risk factors. This study aims to know the relationship among rainfall, temperature, humidity, population density and area of settlement with the incidence of DHF. Research sites in Malang was done by collecting data recorded from the years 2002-2011 from the relevant institutions.The design of this research was time trend ecological study which the unit of analysis is per month and per year during ten years. Data analysis was performed by using univariate, bivariate analysis using correlation and simple linear regression and multivariate analysis using multiple linear regression.The results were statistically showed that the air temperature per year (r=0.705) and area  of settlement (r=0.750) correlated significantly with DHF cases per year with p<0.05, while rainfall, humidity, and the population density did not correlate significantly. Humidity per month ( r=0.618) correlated significantly with DHF cases per month while temperature and rainfall did not correlate significantly. Multivariate analysis predicted that the land area of settlement affected the number of DHF cases as 1,978.Based on the research results, it was concluded that the temperature of the air and  area of settlement correlated significantly with DHF cases per year. While the humidity significantly correlated significantly with DHF cases per month. Government intersectoral collaboration should be enhanced to prevent and eradicate the DHF cases due to environmental changes affected the spread of dengue cases.